PERAN GURU PAI MELALUI PENDEKATAN AKHLAK DALAM MEMBANTU SISWA BERMASALAH DI SMP DHARMA KARYA UT - Lutfi Rahman; Fajriah, Inayah; Eliza Tifanny; Erba Rozalina Yulianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the role of Islamic Religious Education (PAI) teachers using a moral approach to assist problematic students at SMP Dharma Karya UT. A qualitative case study design was employed. Data were collected through in-depth interviews, non-participant observation, and document analysis of student violations and school programs. The findings reveal that PAI teachers contribute by providing personal guidance, religious habituation, exemplary conduct, and empathetic dialogue. The moral approach was implemented through modeling ethical behavior, counseling, spiritual coaching, and worship routines to strengthen students' character development. A collaborative pattern between PAI teachers and guidance counselors enhances the systematic handling of student issues. Supporting factors include strong teacher–student emotional bonds and a religious school culture, while inhibiting factors relate to limited teacher time, insufficient parental support, and negative peer influences. Overall, the moral approach effectively supports behavioral improvement and moral awareness among problematic students.